Asymmetry of tidal currents off the W.Brittany coast and assessment of tidal energy resource around the Ushant Island. (May 2017) - Thiébaut, Maxime; Sentchev, Alexei
Abstract: A method of tidal stream energy resource assessment around the Ushant Island in the Iroise Sea, using surface velocity time series from High Frequency radars (HFR) and ADCP measurements, is presented. Remotely sensed velocities provided by the radars allow to augment the industry standard approach of 3D numerical modeling and in-situ ADCP surveying to make a large-scale quantification of tidal stream resource. They capture the real ocean dynamics and thus provide context on the complex spatial variability of tidal currents that are so often feature at potential tidal energy sites. The observations show current velocities of 4 m/s northwest of the Island and in the Fromveur Strait, with 1 m/s value exceeded 60% and 70% of time respectively. Emphasis is given to the peculiarities in tidal flow asymmetry and to the study of the variation of vertical velocity profiles during different tidal stages. Radar derived velocities reveal a pronounced asymmetry between the flood and ebb flow around the Ushant Island, quantified by dimensionless number a - velocity asymmetry. The largest range of asymmetry variation, from 0.5 to 2.5, is observed in the Fromveur Strait. Harmonic analysis demonstrated that a joint variation of phase of the principal semi-diurnal (M2 ) and quarter-diurnal (M4 ) tidal velocity component accounts for flow asymmetry variation in the strait. Asymmetry in current direction is also quantified. ADCP measurements show that the vertical velocity profiles follow a 1/α power law with a power law exponent mostly depending on geographic location than on tidal stage. It was demonstrated that, in the Fromveur Strait, the 1/7 power law is appropriate to characterize the velocity profile. The combination of two sources of data enables characterization of the velocity variations in three spatial dimensions and in time thus increasing accuracy of the hydrokinetic resource assessment from HF radar observations. The estimation shows that the mean technical resource is 50% smaller in the lower half than in the upper half of the water column. The theoretical resource on average is three times higher than the technical resource and appears to be more sensitive to variations in the shape of the velocity profile in the lower layer. Highlights: A novel method of assessing the hydrokinetic resource at promising tidal stream energy sites in the Iroise Sea is presented. By merging surface velocity time series from HF radars with ADCP data, the major metrics of the tidal flow are quantified. Current velocities show a pronounced asymmetry between the flood and ebb flow varying in a range from 0.5 to 2.5. The 1/7 power law is appropriate to characterize the velocity profile, during at least 3-h period of the strongest flow. Time series of the theoretical and technical power were reconstructed in the lower and upper half of the water column.